Ceramide synthases in cancer therapy and chemoresistance. (April 2019) - Brachtendorf, Sebastian; El-Hindi, Khadija; Grösch, Sabine
Abstract: Drug resistance is one major reason for failure of cancer therapy. In the past 10 years, evidence emerged showing that ceramides of specific chain length, generated by six different ceramide synthases (CerS), are deregulated in different cancer types thereby influencing chemosensitivity. In this review we sum up the cellular mechanisms regulated by CerS and the respective ceramides of specific chain length contributing to chemoresistance and how we can interfere with these mechanisms to overcome drug resistance by targeting CerS. We compile an overview of the different cellular effects influenced by CerS in dependency of the used drug and cancer type. Finally, the potential of CerS as new drug targets in chemotherapy or as biomarkers for the prediction of therapeutic response rates is discussed.